2013
DOI: 10.1007/s10695-013-9859-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger- and garlic-supplemented diet on growth performance, some hematological parameters and immune responses in juvenile Huso huso

Abstract: Physiological parameters and growth performance of Huso huso fingerlings fed with diet supplemented with herbal plants were studied in this study. Dietary treatments were 0 g (= control), 1.0 g (garlic) and 1.0 g (ginger) of 100 g(-1) feed for 60 days. Specific growth rate, body weight gain and condition factor were significantly increased in ginger treatment at the end of the trial. Highest levels of erythrocyte and hematocrit were observed in fingerlings ginger group after 60 days. Globulin increased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 23 publications
5
17
1
Order By: Relevance
“…Our study demonstrated that after 4-week feeding trial, Japanese seabass WG and SGR were not significantly improved by the garlic when compared with the control group. Similar results also were reported by Kanani et al (2014) and Jahanjoo et al (2018). The variation of FCR and K had the similar trend of Lee et al (2014), while the HSI and SR in the study resembled those reported in Zaefarian et al (2017).…”
Section: Ta B L Esupporting
confidence: 91%
See 1 more Smart Citation
“…Our study demonstrated that after 4-week feeding trial, Japanese seabass WG and SGR were not significantly improved by the garlic when compared with the control group. Similar results also were reported by Kanani et al (2014) and Jahanjoo et al (2018). The variation of FCR and K had the similar trend of Lee et al (2014), while the HSI and SR in the study resembled those reported in Zaefarian et al (2017).…”
Section: Ta B L Esupporting
confidence: 91%
“…However, garlic had no effect on growth performance in other aquatic animals (Jahanjoo, Yahyavi, Akrami, & Bahri, 2018;Kanani, Nobaha, Kakoolaki, & Jafarian, 2014). All of these species similarly with Japanese seabass are carnivorous, providing evidences that effects of garlic on aquatic animals' growth performance are diverse and may not directly connect with animals' feeding habit.…”
Section: Ta B L Ementioning
confidence: 99%
“…Elevated lysozyme level was measured in Crucian carp (Carassius auratus gibelio) (Chen, Wu, Yin, & Li, 2003) and Large yellow croaker (Pseudosciaena crocea) (Jian & Wu, 2003) after feeding the fish with various Chinese herbal. However, unlike this study, lysozyme activity was not influenced in juvenile Beluga (Huso huso) fed with ginger and garlic (Gholipour Kanani et al, 2014) and Nettle (Urticadioica) (Binaii et al, 2014). The increasing trend could be due to lysozyme, a humoral component of the non-specific defense mechanism, that has the ability to prevent the growth of infectious microorganism by splitting ÎČ-1, 4 glycosidic bonds between N-acetylmuramic acid and Nacetylglucosamine in the peptidoglycan of bacterial cell walls (Choi et al, 2008;Secombes, 1996).…”
Section: Discussioncontrasting
confidence: 64%
“…In hemoglobin, no significant effect was observed, either considering each factor or their interaction, consistent with studies evaluating a ginger essential oil supplemented diet for Nile tilapia Oreochromis niloticus (Brum et al 2017) and ginger supplemented diet for beluga (Huso huso) (Kanani et al 2014), in which no effect of the supplemented diets on fish hemoglobin was found.…”
Section: Discussionsupporting
confidence: 87%